(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Background The capacity of individuals with multiple sclerosis to walk and maintain balancewas tested in a randomised control trial to compare the benefits of a Pilates exercise programme totraditional physical therapy sessions. Method Before and after the training, participants were tested ontheir walking speed, balance, trust in their own equilibrium, lung capacity, and mental acuity. ResultsThe Pilates and home exercise groups did not vary from one another on measures of walking speed(p=0.096), perceived walking ability (p=0.165), or fear of falling (p=0.385). Conclusion Pilates has thepotential to improve mobility and stability for persons living with multiple sclerosis. There is no evidencethat this technique is more effective than conventional physical therapy.